Psychological well-being, social adjustment and social responsibility as predictors of achievement motivation among Arab postgraduate students in Malaysia - Grera, Maryem Younes (Human Resource Management Academic Research Society (HRMARS), 2022)
Achievement motivation is a very important element in students’ academic success (Steinmayr et al., 2019). This is especially true at the postgraduate level when students are expected to work independently on research projects. The purpose of the present research was to examine how psychological well-being, social adjustment and social responsibility predicted achievement motivation among Arab postgraduate students in Malaysia. The sample consisted of (137) Arab students currently pursuing their postgraduate studies in Malaysia: (59 Syrians, 32 Yemeni, and 46 Libyans). Data were collected using the Achievement Motivation test (Smith, 2018), Ryff’s psychological well- being test (1989), Social adjustment test (Bell, 1934) and the Social Responsibility Test (Othman, 1979). Multiple Regression Analysis and ANOVA were used to analyse the data. Results showed that psychological well-being, social adjustment and social responsibility were significant predictors of achievement motivation among Arab postgraduate students. Furthermore, social responsibility was the most significant predictor of achievement motivation among Arab postgraduate students. The study also showed that there were differences in psychological well-being, social adjustment, social responsibility and achievement motivation among Syrian, Yemeni and Libyan students. These findings have a special significance as they show the possible contribution of these variables to the achievement motivation of Arab students in the diaspora. This will inform future studies about this population.